Two new species of Neoplecostomus (Siluriformes: Loricariidae) from high altitudes of the upper rio Paraná basin, Brazil - Uzeda, Pedro L. C.; Paiola, Isabel [UNESP]; Cesar, Poliana S. [UNESP]; Okubo, Vitor Kenzo N. [UNESP]; Marques-Frisoni, Wellington J. [UNESP]; Andrade, Breno N. [UNESP]; Langeani, Francisco [UNESP] (FapUNIFESP (SciELO), 2024)
Two new species of Neoplecostomus are described from the headwaters of the rio Sapucaí drainage, affluent of the rio Grande in upper rio Paraná basin. The new species are most similar to each other, and can be diagnosed from congeners by having the exposed area of the first plates of mid-ventral and ventral series narrower than the naked area surrounding each plate; different tooth morphologies and numbers in males and females; arrangement of odontodes on caudal-peduncle plates; size of adipose fin and cranial osteological character states. Both new species are endemic to Serra da Mantiqueira, southeastern Brazil. Some comments are made on their intraspecific variation, genetics, and conservation.
Keywords: Armored catfish; Headwaters; Ichthyofauna; Serra da Mantiqueira; Sexual dimorphism